An endemic new species of Ameiva (Squamata: Teiidae) from an isolated dry forest in southern Peru - Landauro, Caroll Z.; García-Bravo, Antonio; Venegas, Pablo J. (Zootaxa, 2015)
We describe a new species of Ameiva from an interandean dry forest in central-southern Peru. Ameiva reticulata sp. nov. represents the fifth species in the genus known to occur in Peru. The new species is similar to the species of the A. ameiva complex such as A. ameiva, A. atrigularis, A. pantherina, and A. praesignis, and is distinguished from these by  a smaller size, a lower  count of dorsal scales along the middorsal line and scales across the midbody, and by the gular coloration.